2010
DOI: 10.1002/pro.347
|View full text |Cite
|
Sign up to set email alerts
|

Drug binding and resistance mechanism of KIT tyrosine kinase revealed by hydrogen/deuterium exchange FTICR mass spectrometry

Abstract: Mutations of the receptor tyrosine kinase KIT are linked to certain cancers such as gastrointestinal stromal tumors (GISTs). Biophysical, biochemical, and structural studies have provided insight into the molecular basis of resistance to the KIT inhibitors, imatinib and sunitinib. Here, solution-phase hydrogen/deuterium exchange (HDX) and direct binding mass spectrometry experiments provide a link between static structure models and the dynamic equilibrium of the multiple states of KIT, supporting that sunitin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 27 publications
0
17
0
Order By: Relevance
“…Treatment with sunitinib in humans results in the emergence of secondary mutations that render the oncogenic RTK resistant to the effects of sunitinib. Secondary mutations in GIST that render KIT resistant to sunitinib typically map to the A-loop (68)(69)(70) and are thought to shift the kinase toward the active state (67,75,76). Residues that are mutated in KIT include D816, D820, N822, Y823, and A829 (68)(69)(70).…”
Section: Resultsmentioning
confidence: 99%
“…Treatment with sunitinib in humans results in the emergence of secondary mutations that render the oncogenic RTK resistant to the effects of sunitinib. Secondary mutations in GIST that render KIT resistant to sunitinib typically map to the A-loop (68)(69)(70) and are thought to shift the kinase toward the active state (67,75,76). Residues that are mutated in KIT include D816, D820, N822, Y823, and A829 (68)(69)(70).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, we consider a disturbing effect on the JM-Switch folding as indicative of the JMR departure from its inhibitory position and general effect induced by KIT hotspot mutations. Such departure of JMR from the kinase domain favors the stabilization of the inactive non-autoinhibited state [107], [108], where the JMR displays an increased solvent accessibility, as was revealed by hydrogen/deuterium exchange mass spectrometry analysis of KIT D816H and KIT V560D mutants [107]. Nevertheless, the contribution of this change to KIT activation is different in the two kinds of mutation – in the A-loop and in the JMR.…”
Section: Discussionmentioning
confidence: 97%
“…It was shown that imatinib binds to the inactive non-autoinhibited state in which the JMR is detached from the kinase domain [107], [108]. The inactive non-autoinhibited conformations of KIT V560G/D mutants, which is induced by JMR detachment from the kinase domain, would be the most appropriate targets for imatinib binding.…”
Section: Discussionmentioning
confidence: 99%
“…HDX studies of a mutant form of the tyrosine kinase c-Kit that is associated with gastrointestinal stromal tumors indicate that the D816H mutation, at the N-terminus of the activation segment, increases solvent-accessibility at the C-terminal end of the activation segment (29). Similar to the sequence changes that we introduced into Itk to produce the activated Itk_Btk loop-6 mutant, a change in activation loop dynamics induced by the D816H mutation of c-Kit correlates with a higher rate of autophosphorylation compared to that of the wild-type kinase (29). Indeed, it is likely that many disease-causing mutations fundamentally alter protein dynamics, which leads to functional deregulation.…”
Section: Discussionmentioning
confidence: 99%